Artists as professors: Poetic reflections on acts of negotiation, Part Iof IV. Issue 2 (17th May 2012) - Bowman, Harrigan McMahon
This reflective piece considers how one art professor describes the potential for a balance in the distinct roles of artist and educator that are embedded in her practice as an art professor. It is a compilation of the descriptions of a professor who was interviewed for the dissertation research of Harrigan McMahon Bowman of Columbia University in 2010. Four professors of art who were all publicly recognized for their accomplishments in teaching were interviewed regarding the relationship between these two roles (among others) within their practice. The four models of negotiation found in the qualitative case-studies were those of Complete Separation, Complete Integration, See-Saw: A Fragile Balance, and Total Commitment: A Sacrificial Balance. Presented in this first writing in a series of four, Danielle Bauer represents the model of Complete Separation. In her own words, extracted from her interviews, she describes her understanding of herself and how she came to be an art professor. This reflection will be followed by similar reflective representations of the three further found models of negotiation.